Adolescent neurocognitive development and impacts of substance use: Overview of the adolescent brain cognitive development (ABCD) baseline neurocognition battery. (August 2018) - Luciana, M.; Bjork, J.M.; Nagel, B.J.; Barch, D.M.; Gonzalez, R.; Nixon, S.J.; Banich, M.T.
Abstract: Adolescence is characterized by numerous social, hormonal and physical changes, as well as a marked increase in risk-taking behaviors. Dual systems models attribute adolescent risk-taking to tensions between developing capacities for cognitive control and motivational strivings, which may peak at this time. A comprehensive understanding of neurocognitive development during the adolescent period is necessary to permit the distinction between premorbid vulnerabilities and consequences of behaviors such as substance use. Thus, the prospective assessment of cognitive development is fundamental to the aims of the newly launched Adolescent Brain and Cognitive Development (ABCD) Consortium. This paper details the rationale for ABC'lected measures of neurocognition, presents preliminary descriptive data on an initial sample of 2299 participants, and provides a context for how this large-scale project can inform our understanding of adolescent neurodevelopment.